Affectivity and academic performance in the language area - Espinel Mesa, Omaira Milena; Samacá Pesca, Graciela del Carmen; Cristancho Altuzarra, José Gabriel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents the results of the research entitled “Affectivity and academic performance in the Language Area”, through the implementation of a pedagogical proposal as a methodological strategy to develop emotional competencies that strengthen the learning process and contribute to the integral development of students of the second and fourth grades of Primary School of the Educational Institution Ramón Ignacio Avella in Aquitania (Boyacá, Colombia). The work has been developed with a criticalsocial approach and through an action research, systematizing and analysing the pedagogical practices of teachers.  This process has involved students and parents in the development of activities for change as opposed to attitude and commitment to the process of formation in the affective and cognitive planes. As results of the research, the social, cultural and family inconsistencies that directly affect the academic process and the integral development of the child are identified, a situation that requires that society, managers and teachers act as managers of conducive environments for education.